AN ANALYSIS OF TEACHERS’ CODE SWITCHING IN TEACHING LEARNING PROCESS AT PRIBADI BILINGUALBOARDING SCHOOL BANDUNG - Amalia Hibatul Wafi; Tenia Ramalia; Isnaniah, Isnaniah (Cahaya Ilmu Bangsa Institute, 2024)
The purpose of this study is to describe the form of code switching in classroom interaction used by English teachers at SMP Pribadi Bilingual Boarding School Bandung. This research uses descriptive qualitative method which is used to describe clearly about the fact of code switching based on its form according to the data obtained by recording the teacher's language in the process of classroom interaction, and using field notes that can support the recording data. The object of this research is English teachers consisting teachers, namely male teachers and female teachers who teach at SMP Pribadi Bilingual Boarding School Bandung. The findings of the data analysis show that the types of code switching are found in three types: inter-sentential code switching, intra-sentential code switching, and tag code switching. The functions of code switching used by English teachers were found in three functions: topic switching, affective function, and repetitive function. In addition, the languages involved in the code-switching process are in the form of inter-language relations (English to Indonesian and Indonesian to English) and in the form of language use (formal language and informal language).